Drill bit design and its effect on temperature distribution and osteonecrosis during implant site preparation: an experimental approach - Islam, Md. Ashequl (2023)
In this study, the drilling parameters will be evaluated to obtain optimal parameters in minimizing the impact of drilling damage on synthetic bone blocks. The effect of damage observed in the study is osteonecrosis that occurs in the drill hole for implant site preparation, where a smaller value is desired. The drilling parameters are optimized using the Taguchi method with two control factors: the feed rate and spindle speed; each parameter is designed in five levels. This experiment was then carried out on four different designs of drill bits, i.e., Twist (118°and 135°), spherical, and conical drill bits. While experimental planning uses L25 orthogonal arrays, the "smaller is better" approach is used as a standard analysis. The main findings of this research are 118° point angle twist drill bit is the ideal type of drill bit for bone drilling, as it produces less heat than other types of drill bits. The optimal range of feed rate and drilling speed for bone drilling is 40-60 mm/rev and 1000-1400 RPM, respectively. Combining these parameters helps to minimize heat generation during implant site preparation drilling.